Factors influencing teachers'choice and use of tasks for formative assessment of mathematics in grades 2-6 - Wilson Thompson, Bronwen (My University, 2006)
Abstract This study explores teachers’ understanding about ways in which assessment supports learning and teaching within the context of grappling with the new curriculum. It argues that formative assessment, supports a socialconstructivist view of learning and teaching. It suggests that formative assessment functions in a fundamentally different way to summative assessment, and could assist teachers in moving towards a more conceptual approach to learning and teaching. Teachers’ views are explored in focus groups in which teachers discuss their choice and use of either traditional or alternative assessment tasks, in their mathematics lessons. The findings suggest, however, that teachers’ ability to use assessment in this way is influenced by their own views of mathematics learning, their current views of assessment, the amount of support provided in the assessment materials, and the practices of the school. Key words Formative assessment Social constructivist Focus groups Phenomenography Primary school Mathematics Assessment Investigations
MEd thesis
Keywords: Formative assessment; Focus groups; Phenomenography; Primary school; Mathematics; Assessment; Investigations; Social Constructivist